A jogász szakmát érintő zsidóellenes intézkedések az első Szlovák Köztársaságban (1939–1945) - Halász, Iván (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The paper deals with the Anti-Jewish policy of the first Slovak Republic during the second world war. The prewar Slovakia was the part of democratic Czechoslovakia, which guaranteed good (equal) legal position for Jews. Slovakia in October 1938 achieved autonomy and in March 1939 declared independency. The Anti-Jewish policy started after these events. The rate of this policy was very dramatic and fast. Firstly Slovakia realised non-racial discriminative policy based mostly on the principle of numerus clausus and intensive discrimination, but after 1940 this tendency changed and Slovak governmental policy followed the Nazi-German model. The first Anti-Jewish measures affected the legal profession and journalist more intensively then other intellectual professions, because Slovak lawyers „attacked” the legal positions in public administration and advocacy. Later this disproportion was not typical and the general discriminative policy affected every segments of Jewish community in equal form.